Comparison and evaluation of seven different bench‐top flow cytometers with a modified six‐plexed mycotoxin kit. Issue 12 (3rd September 2013) - Czeh, Arpad; Schwartz, Abe; Mandy, Frank; Szoke, Zsuzsanna; Koszegi, Balazs; Feher‐Toth, Szilvia; Nagyeri, Gyorgy; Jakso, Pal; Katona, Robert L.; Kemeny, Agnes; Woth, Gabor; Lustyik, Gyorgy
Abstract Many bench‐top flow cytometers (b‐FCs) are compatible with microsphere‐based multiplexed assays. Disciplines implementing b‐FCs–based assays are expanding; they include monitoring and validating food quality. A multiplexed platform protocol was evaluated for poly‐mycotoxin assays, which is compatible with a variety of b‐FC models. The seven instruments included: BD FACSCalibur™, BD FACSArray™ Bioanalyzer, Accuri C6, Partec CyFlow® Space, Beckman Coulter FC 500, Guava EasyCyte Mini, and Luminex 100 ™. Current reports related to the food industry describe fungal co‐infections leading to poly‐mycotoxin contamination in grain (Sulyok M, Berthiller F, Krska R, Schuhmacher R, Rapid Commun Mass Spectrom 2006;20:2649–2659). It is imperative to determine whether b‐FC–based assays can replace traditional single‐mycotoxin enzyme‐linked immunosorbent assay (ELISA). A six‐plexed poly‐mycotoxin kit was tested on seven different b‐FCs. The modified kit was initially developed for the BD FACSArray™ Bioanalyzer (BD Biosciences) (Czeh A, Mandy F, Feher‐Toth S, Torok L, Mike Z, Koszegi B, Lustyik G, J Immunol Methods 2012;384:71–80). With the multiplexed platform, it is possible to identify up to six mycotoxin contaminants simultaneously at regional grain collection/transfer/inspection facilities. In the future, elimination of contaminated food threat may be better achieved with the inclusion of b‐FCs in the food protection arsenal. A universal protocol, matched with postacquisition software, offers an effective alternative platform compared to using a series of ELISA kits. To support side‐by‐side evaluation of seven flow cytometers, an instrument‐independent fluorescence emission calibration was added to the protocol. All instrument performances were evaluated for strength of agreement based on paired sets of evaluation to predicate method. The results suggest that all b‐FCs were acceptable of performing with the multiplexed kit for five of six mycotoxins. For OTA, the detection sensitivity was consistent only for five of the seven instruments. © 2013 International Society for Advancement of Cytometry